2018
DOI: 10.1177/2041669518781381
|View full text |Cite
|
Sign up to set email alerts
|

Visual Light Zones

Abstract: In this article, we studied perception of a particular case of light fields that is characterized by a difference in its consistent structure between parts of a scene. In architectural lighting design, such a consistent structure in a part of a light field is called a light zone. First, we explored whether human observers are sensitive to light zones, that is, zones determined primarily by light flow differences, for a natural-looking scene. We found that observers were able to distinguish the light conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…The scenes included a variety of colored surfaces in both rural and urban settings. They were chosen to contain surfaces that were partly lit by sunlight and partly in the shade as to capture two light zones [42,43] in the light field. In each of the 24 scenes, the local light fields of the sample points in the light and shade were acquired within 1 minute, yielding a total of 48 local light field measurements.…”
Section: Measurements Of Natural Light Fieldsmentioning
confidence: 99%
“…The scenes included a variety of colored surfaces in both rural and urban settings. They were chosen to contain surfaces that were partly lit by sunlight and partly in the shade as to capture two light zones [42,43] in the light field. In each of the 24 scenes, the local light fields of the sample points in the light and shade were acquired within 1 minute, yielding a total of 48 local light field measurements.…”
Section: Measurements Of Natural Light Fieldsmentioning
confidence: 99%
“…Observers can adjust the intensity, direction and diffuseness of illumination on spherical probes at different locations with reasonable accuracy within a simple photographed scene (Koenderink et al, 2007) or in real scenes (Xia, Pont, & Heynderickx, 2014, 2017c. Light field estimates are somewhat simplified compared to ground truth structure, and biased toward diverging light fields (i.e., light radiating from a source; Kartashova, Sekulovski, de Ridder, te Pas, & Pont, 2016) but do represent different 'light zones' (Kartashova, de Ridder, te Pas, & Pont, 2018). Gilchrist (1977) demonstrated that observers' reflectance judgements can change dramatically depending on the perceived location, and therefore the perceived local illumination of a surface patch.…”
Section: Illumination Distribution Over Spacementioning
confidence: 99%
“…Although our perception of illumination has received insufficient psychophysical examination (Gilchrist, 2006 ; Schirillo, 2013 ), there is evidence that the visual system infers the lighting conditions in a scene. Observers can estimate the properties of a light source based on an object’s appearance (Kartashova, Sekulovski, de Ridder, te Pas, & Pont, 2016 ; Kartashova, de Ridder, te Pas, & Pont, 2018 ; Koenderink, Pont, van Doorn, Kappers, & Todd, 2007 ) and these estimates are evident in observers’ perception of surface reflectance (Boyaci, Maloney, & Hersh, 2003 ; Boyaci, Doerschner, & Maloney, 2004 ). Furthermore, the lighting conditions at different spatial locations in a scene can be accounted for when judging surface reflectance (Gilchrist, 1977 , 1980 ; Mizokami, Ikeda, & Shinoda, 1998 ), with the observers relying on information given by multiple lighting cues (e.g., specular and non-specular objects) within a scene to make their judgements (Boyaci, Doerschner, & Maloney, 2006 ; Snyder, Doerschner, & Maloney, 2005 ).…”
Section: Introductionmentioning
confidence: 99%